Kepatuhan Ibu Hamil Dalam Konsumsi Tablet Tambah Darah Dengan Kejadian Berat Badan Lahir Rendah - Rahim, Eman; Waluyo, Darmayanti; Maesarah, Maesarah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Birth weight in infants is associated with a decrease in the immune system of pregnant women, one of which can be caused by iron deficiency, for this reason, it is necessary to have blood-added tablets for pregnant women to avoid anemia. but in fact, there are still many pregnant women who do not comply with the rules of consuming blood-added tablets. this will impact the occurrence of pregnancy problems or cause the baby to be born to have a low weight. The purpose of this study was to determine the relationship between adherence to taking blood tablets and the incidence of low birth weight. Using an observational design with a cross-sectional approach with a sample of 32 people using total sampling, the data obtained were analyzed using chi-square The results obtained p-value is 0.401, which means that there is no significant relationship between adherence to blood-added tablet consumption and the incidence of low birth weight. Compliance with blood tablet consumption does not directly relate to the incidence of low birth weight.